2017
DOI: 10.1007/s13201-017-0601-x
|View full text |Cite
|
Sign up to set email alerts
|

Metallic iron for water treatment: leaving the valley of confusion

Abstract: Researchers on metallic iron (Fe 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 223 publications
(314 reference statements)
0
57
0
Order By: Relevance
“…Recent investigations have shown that the true problem of Fe 0 filters is the time-dependent loss of permeability [66][67][68]. According to Makota et al [67], 'reactivity loss' is a mirage as it is just the natural decrease of the corrosion rate which is never a linear function of time [35].…”
Section: The Service Life Of Fe 0 Filtersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations have shown that the true problem of Fe 0 filters is the time-dependent loss of permeability [66][67][68]. According to Makota et al [67], 'reactivity loss' is a mirage as it is just the natural decrease of the corrosion rate which is never a linear function of time [35].…”
Section: The Service Life Of Fe 0 Filtersmentioning
confidence: 99%
“…According to Makota et al [67], 'reactivity loss' is a mirage as it is just the natural decrease of the corrosion rate which is never a linear function of time [35]. In other words, if a proper material is selected, the major remaining task is to control the hydraulic conductivity (permeability).…”
Section: The Service Life Of Fe 0 Filtersmentioning
confidence: 99%
“…As it is now established that systematic flaws were governing research on Fe 0 for environmental remediation [35,44,45,53,55,[57][58][59][60][61], there have been some injustice within the research community. In particular, the demands for research money is much larger than the supply.…”
Section: The Assessment Of the Peer Review System Questionedmentioning
confidence: 99%
“…The situation is worsen by the evidence that the Fe 0 filtration technology was introduced by distorting the stream of corrosion science and overseeing many other aspects of General Chemistry. In particular, the favoured reductive transformation concept is even not valid in the concentration range of concern (µg/L) [38,53,56,57]. Thus a paradigm shift of the current understanding for Fe 0 filtration technology is very much demanding before the future researchers are dragged deeper into confusion [95].…”
Section: Should Scientists Learn From Politicians?mentioning
confidence: 99%
See 1 more Smart Citation